The Effects of Brand Equity towards Customer Loyalty of a Well-known Sportswear Brand in Malaysia - Tan, Yew Huei; Huam, Hon Tat; Ahmad, Sharifuddin; Amran, Rasli; Mohamad Rozi, Hassan; Nasser, Noor (2010)
Purpose - Given the rising number of brands available in the country, there may be a corresponding rise in customer loyalty towards their preferred brand. There are many reasons why customers remain loyal to their favorite brand. One reason is brand equity. The purpose of this research is to examine the relationship between brand equity and customer loyalty towards a well-known sportswear brand among students attending one of the public universities in Malaysia. Methodology – In order to carry out this research, a quantitative research approach was used. A questionnaire was developed and randomly distributed to 300 respondents. Reliability analysis, Person correlation analysis and multiple regression analysis were used to analyze the data. Findings – The result of this research suggests that satisfaction, resistance to change and affect are consistently the most important dimensions that influence customer loyalty. However, based on this research, it shows that trust and value have no significant relationship with customer loyalty. Future Research – One of the limitations in this research is that some respondents were not serious in answering the questionnaire. In addition, the population of this research was only among students in the university. As a result, the analysis may not be generally applied. Therefore, it is recommended that future researchers conduct similar research in a larger population in order to get a more reliable and accurate result. Originality/value – This research provides a valuable insight into a well-known sportswear brand, or even the sportswear industry, and contributes to a greater understanding of the success factors manufacturers need to focus on in order achieve a high level of customer loyalty.